2009
DOI: 10.1038/onc.2009.135
|View full text |Cite
|
Sign up to set email alerts
|

An integrated genomic analysis of lung cancer reveals loss of DUSP4 in EGFR-mutant tumors

Abstract: To address the biological heterogeneity of lung cancer, we studied 199 lung adenocarcinomas by integrating genome-wide data on copy number alterations and gene expression with full annotation for major known somatic mutations in this cancer. This revealed non-random patterns of copy number alterations significantly linked to EGFR and KRAS mutation status and to distinct clinical outcomes, and led to the discovery of a striking association of EGFR mutations with under-expression of DUSP4, a gene within a broad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
227
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(246 citation statements)
references
References 38 publications
19
227
0
Order By: Relevance
“…S6 C and D). We next carried out a similar analysis in a collection of CRC tumor samples characterized by The Cancer Genome Atlas (the TCGA colorectal tumors) (33) and a combined set of lung tumor samples (the Tomida_Chitale lung tumors) (1,3). We again observed a modest but consistent negative correlation between the ERH and the Singh and Bhattacharjee signature scores in these samples (Fig.…”
Section: Erh Regulates the Expression Of A Subset Of Genes Involved Imentioning
confidence: 71%
See 1 more Smart Citation
“…S6 C and D). We next carried out a similar analysis in a collection of CRC tumor samples characterized by The Cancer Genome Atlas (the TCGA colorectal tumors) (33) and a combined set of lung tumor samples (the Tomida_Chitale lung tumors) (1,3). We again observed a modest but consistent negative correlation between the ERH and the Singh and Bhattacharjee signature scores in these samples (Fig.…”
Section: Erh Regulates the Expression Of A Subset Of Genes Involved Imentioning
confidence: 71%
“…synthetic lethality | spliceosome T he Ras family of small GTPases is mutated in a significant fraction of human cancers, with high frequencies of mutations in v-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog (KRAS) found in colon, lung, and pancreatic cancers (1)(2)(3)(4). Ras proteins are activated by growth factor receptors, and they, in turn, activate a number of downstream effector pathways to coordinate cell proliferation, survival, and migration.…”
mentioning
confidence: 99%
“…1A and Table S2). The most frequent CNAs observed were gain of chomosome 3q, which harbors PIK3CA and is amplified in many cancers; loss of chromosome 3p, which harbors FHIT, TGFBR2, and FOXP1 and is frequently lost in epithelial cancers; and loss of chromosome 8p, which harbors NKX3 and DUSP4 (30)(31)(32)(33). EGFR/PI3K pathway genes within regions of significant copy number gain included PIK3CA (frequency = 45.2%, q = 7.45 × 10 −7 ), RIC-TOR (frequency = 38.7%, q = 1.12 × 10 −4 ), and EGFR (frequency = 32.3%, q = 3.42 × 10 −5 ).…”
Section: Resultsmentioning
confidence: 99%
“…(D) Clinical outcome by PTPRS expression in lung adenocarcinomas with TKI-sensitive EGFR mutations. Cases treated at Memorial Sloan-Kettering Cancer Center were categorized as low (below median) or normal PTPRS expressors, and recurrence and survival were calculated using the Kaplan-Meier method and a log-rank test (31).…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have examined LCINS for multiple mutations, including EGFR and KRAS mutations, but did not include ALK rearrangements. 41,45 More recently, Sun et al reported multiple genetic alterations in lung adenocarcinoma samples from never-smokers. However, those authors did not examine survival outcomes after chemotherapy or EGFR TKI treatment and only investigated a small patient cohort.…”
Section: Discussionmentioning
confidence: 99%